Cross Cultural Differences in Essentialist Beliefs about Religion Categories: Comparing Northern Ireland to the US - Feeney, Aidan (Journal of cognition and culture, 2026)
To examine cultural differences in beliefs about social categories, two studies examined whether there are differences between Northern Ireland and the US in the strength of essentialist beliefs about eleven social dimensions including culturally salient dimensions of religion and race. In both studies religion categories were essentialized more by participants in Northern Ireland who viewed them as more natural but no more cohesive than US participants. Essentialist beliefs about race categories did not differ cross-culturally. In general, these findings suggest that - as in the case of belief about religion categories in Northern Ireland - social categories may be essentialized because they are culturally salient or in the absence of salience - as in the case of beliefs about race categories in Northern Ireland - because of more general conceptual proclivities. These findings also suggest a potentially important role for ontological beliefs about religion categories in the formation of religious prejudice.